MASA THE GOLDEN AGE DAN KEMUNDURAN DINASTI ABBASIYAH - Azizah Nurtanti; Nuryuana Dwi Wulandari (Universitas Negeri Gorontalo, 2023)
The Bani Abbasiyah period was the peak of its glory that occurred during the reign of Caliph Harun ar-Rashid and his son Al-Maksum. The Abbasiyah experienced setbacks and destruction when the Mongol invasion appeared, led by Halagu Khan in 1258 H. Types and methods of historical research. This study aims to find out about the golden age and the decline of the Abbasiyah dynasty at that time. In collecting data, the authors use the method of literature research (library research). The collected data is then read and recorded for processing and analysis as research material. The type of data used consists of books, e-books, and articles on websites. The Golden Age of the Abbasiyah dynasty and Islamic culture reached its glory during the Abbasiyah dynasty which emphasized the development of Islamic civilization and culture rather than expanding territory. The factors that resulted in the decline and destruction of the Abbasiyah dynasty were due to two factors, namely internal and external factors. The Abbasiyah dynasty experienced the golden age, excelling in the fields of translation, science, economics, religion, social, military, and also in politics. The decline of the Abbasid dynasty was caused by 2 factors, namely internal and external. From the internal factors of the decline of the Abbasiyah dynasty, the most dominant influence on the decline of the Abbasiyah dynasty was that Muslims abandoned their religious teachings.